Dualitas Gelombang Partikel sebagai Metafora untuk Ekonomi Koperasi: Studi Interdisipliner - Franklin Kharisma Genta (LPPM Universitas Koperasi Indonesia, 2025)
This study aims to analyze the dynamics of production cooperatives in West Java using an interdisciplinary metaphorical approach based on the theory of wave–particle duality in quantum physics. This approach conceptualizes cooperatives as systems composed of two primary dimensions, economic logic and social logic. The research method employed is qualitative-narrative, combining systems analysis with metaphorical interpretation. Secondary data were obtained from Statistics Indonesia (BPS), the West Java Office of Cooperatives and SMEs, and the Ministry of Cooperatives and SMEs for the period 2019–2024. The findings indicate a positive growth in both the number of cooperative units and membership, however their contribution to the Regional Gross Domestic Product (RGDP) remains relatively stagnant. This phenomenon suggests an imbalance between institutional development and economic outcomes. The study formulates a conceptual and mathematical model of cooperatives as a wave function, representing a superposition of social and economic values that collapse into tangible actions through collective decision-making processes, such as the Annual General Meeting. The wave–particle duality framework offers a novel contribution to understanding cooperatives as dynamic quantum-social systems and provides an alternative analytical lens to coherently integrate their economic and social dimensions.